IMPLEMENTASI VONIS NIHIL DALAM SISTEM PERADILAN INDONESIA - KMS Herman; Agus Sudrajat; Verania Hedi Permata (Fakultas Hukum Universitas Borobudur, 2023)
Indonesia is a constitutional state and all Indonesian citizens must uphold the law in their daily lives, and those who do not comply with it are said to have violated the law which can be in the form of a crime that must be held criminally accountable based on a judge's decision (verdict). The purpose of this study is the setting of zero sentences in indonesian legislation and its application in the Indonesian judicial system. This research is a normative legal research using statutory and contextual approaches. The source of legal materials for this research comes from primary legal materials which are the Criminal Code and the Criminal Procedure Code, supported by secondary sources, namely legal books and journals that are relevant to this research. The results of this study are that the provisions regarding nihi sentences can be found in Article 67 of the Criminal Code which states that if a person is sentenced to death or life imprisonment, besides that, no other punishment may be imposed except for the revocation of certain rights, and the announcement of the judge's decision, besides that there is in Article 65 of the Criminal Code in the event that concurrently is subject to the same basic punishment, then only one sentence is imposed. The application of a nil sentence is carried out on a cumulative sentence with a certain time to limit a person not to be convicted beyond the sentence limit or the sentence for a certain time may not exceed 20 years as stated in Article 12 paragraph (4) of the Criminal Code.